CO-DESIGN DUAL BAND LNA DAN BANDPASS FILTER UNTUK GROUND CHECK MONITORING PADA RADIO NAVIGATION AIDS - Muh Wildan; Toni (Langit Biru: Jurnal Ilmiah Aviasi, 2016)
In this research discusses the design circuit co-design dual-band LNA and BPF at Radio Navigation Aids (RNA) in particular equipment Very High Frequency Omni Range (VOR) / Instrument Landing System Localizer (ILS LOC) working at band working on band VHF 108-118 MHz and ILS Glide Slope (GP) on band UHF 328.6 MHz - 335.4 MHz are used for ground check monitoring. The co-design is a series of LNA and BPF are combined in a circuit. Bandpass filters are designed also serves as a substitute for the output matching impedance of the LNA, so it has the advantage of passive components becomes less and dimensions of the devices become smaller, but still have same performance with a dual-band LNA and BPF are designed in cascade by the conventional method. For comparison also designed a dual-band LNA circuit without dual band BPF and a dual band LNA and BPF in cascade. Simulation results show good performance in all curcuits. In a co-design for the center frequency of 113.0 MHz and 332.0 MHz frequencies obtained consecutive gain (S21) 24.116 dB/17.213 dB, input return loss (S11) -24.885 dB/-30.223 dB, noise figure 1.283 dB/ 1.250 dB, stability factor 1.159 / 1.778 and VSWR 1.121 dan 1.064. While the value of the measurement results of fabrication equipment and input return loss gain slightly decreased the value of simulation results but still meet the design specifications for the VHF band, UHF band but still out of tolerance from the design specifications